Faktor yang berhubungan dengan Siklus Menstruasi pada Mahasiswi Tingkat Akhir di DKI Jakarta - Badzlina, Fildzah; Septiarani, Khoirunnisa; Rahayu, Nur Setiawati (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Menstruation is a process of endometrium shedding in women that happens every month. The normal menstrual cycle occurs in 21 ?? 35 days, with an average of 28 days. The menstrual cycle will be disrupted if reproduction hormones in the body are unstable, thus causing health impacts, such as endometriosis, polycyclic ovarium syndrome, infertility, and signs of cancer. Purpose This study aimed to find out any correlation between sources of phytoestrogen consumption, physical activity level, and stress level to menstrual cycle on final-year students who live in DKI Jakarta. Method This study used quantitative descriptive methods with a cross-sectional design. The total number of participants in this study is 96 participants. Data has been collected is tested with a cross-tabulation test with a confidence interval of 95%. Results Based on the chi-square test, the results show that there is no correlation between phytoestrogen intake with the menstrual cycle (p-value 0,838) and stress level with the menstrual cycle (p-value 0,290). Based on fisher??"s exact test, the result shows that there is no significant correlation between physical activity level with the menstrual cycle (p-value 0,336).